Pemanfaatan Media Digital untuk Pengajaran Al-Qur'an dan Hadis di Era Digital - Saripuddin B, Muhammad (Pusdikra Publishing, 2024)
The utilization of digital media in teaching the Qur'an and Hadith has become a strategic step to enhance the quality of Islamic education in the digital era. This study aims to explore the potential, benefits, and challenges of using digital media in Qur'an and Hadith learning. Using a qualitative approach and case study method, data were collected through interviews, observations, and document analysis at several Islamic educational institutions that have integrated digital technology. The findings reveal that digital media, such as Qur'an learning applications, online tafsir platforms, and interactive videos, provide flexibility and interactivity that enhance students' understanding of the material. However, challenges such as limited access to technology, low digital literacy, and concerns over content alignment with Islamic values are significant barriers to implementation. The study also highlights the importance of collaboration between educators, students, parents, and policymakers to optimize the benefits of digital media in Islamic education. In conclusion, digital media can serve as an effective tool for supporting Qur'an and Hadith learning when used wisely and responsibly. Investment in digital infrastructure, digital literacy training for educators, and the development of Islamic-specific platforms are critical steps to address these challenges. This research contributes to the development of relevant and innovative Islamic educational practices in the digital era.